Local perceptions and endogenous knowledge of Hoary Basil (Ocimum americanum L.) in Burkina Faso - Kabore, Hervé; Kibere, Mariam; Nanema, Kiswendsida Romaric (Ethnobotany Research and Applications, 2023)
Background: Ocimum americanum is an aromatic species from the family of Lamiaceae. It has significant socioeconomic potential and is used by the local population in Burkina Faso. Although the species makes a significant contribution to household well-being, the organizations in charge of natural resource management are unaware of and undervalue its socioeconomic value. This study was initiated to assess local communities’ perception of the uses and management techniques of Ocimum americanum to establish sustainable strategies for its better valorization. Methods: An ethnobotanical survey was conducted in 21 villages covering three phytogeographical sectors of Burkina Faso. All, 160 farmers were interviewed. Relative frequency of citation (RFC) and use value (UV) were used to express the results. Results: The results showed that socio-cultural factors significantly affect the use value of the species at a threshold of 5%. The primary uses of wild basil are traditional medicine, food, conservation of seeds and foodstuffs, fodder, insect repellant, and tradimystics. The species is still found in the wild, although the majority of informants (54.9%) reported a decline in its population, making it threatened with extinction. However, for beneficial purposes, 24.5% of respondents keep the species in paraculture. Conclusion: This study demonstrates how important this species is to local communities. The endogenous knowledge collected among the local population could serve as a baseline for the valuation of the species. Keywords: Ocimum americanum, ethnobotanical survey, endogenous knowledge, Burkina Faso